Emerging antibiotic resistance: a modern-day horseman of the apocalypse - Gómez-Piña, Juan José; Luna, Vanessa Castro; Alfaro, Natalia León; Reyes, Abraham Gilberto Medina; Pérez, Citlalli Piña; Puebla Valdés, Nallely; Acevedo , Arturo Olvera (International Journal of Research in Medical Sciences, 2024)
Background: Antimicrobial resistance (AMR) has emerged as a global public health crisis, posing a significant threat to the effectiveness of antimicrobial agents. Mexico, faces a daunting challenge in tackling the rising prevalence of AMR. The misuse and overuse of antimicrobial drugs, inadequate infection control practices, and a lack of awareness among healthcare providers and the general public have all contributed to the rapid spread of resistant pathogens in the country. We aimed to determine the prevalence of antimicrobial resistance in patients hospitalized from January 2018 to December 2019 Methods: In this study, we analyzed blood, urine, wound, expectoration, and secretion cultures from January 2018 to December 2019 to assess antimicrobial resistance in our unit. We collected patient data, evaluated isolates using EUCAST and CLSI breakpoint tables, and excluded intrinsically resistant antibiotics. A circus plot graph was created to compare resistance profiles between the two years. SPSS version 25 and R Studio software were used for statistical analysis and visualization. Results: AMR increased across diverse organisms (2018-2019), notable rises in A. xylosoxidans (cefuroxime, ciprofloxacin), A. baumannii (piperacillin/tazobactam, ceftazidime), E. coli (ampicillin/sulbactam), K. pneumoniae (ceftazidime), P. aeruginosa (cefuroxime) were observed. Enterococcus faecalis displayed lowest resistance to nitrofurantoin/tobramycin, but highest to fosfomycin. Escherichia coli showed significant resistance to aztreonam, ampicillin/sulbactam, trimethoprim/sulfamethoxazole. Pseudomonas aeruginosa exhibited concerning levels of resistance to ceftriaxone, ampicillin/sulbactam, ceftazidime. Conclusions: AMR in our unit raise concerns for empiric therapy and infection control. Emerging resistance in key pathogens demands enhanced surveillance, rapid response, and robust infection control strategies, including meticulous hygiene, disinfection, antimicrobial stewardship, and resistance monitoring. Continuous optimization is crucial to combat this escalating public health threat in Mexico.